Microstructural and mechanical characterisation of injection molded inconel 718 superalloy - Koh, An Song (2017)
Powder injection molding (PIM) of Superalloy is popular due to its cost effectiveness and capability to mass produce complex components. Inconel 718 (IN718) is a type of nickel-based Superalloy which has high-strength and corrosion-resistant at high temperature. For PIM process, IN718 feedstock needs to be prepared which consist of the raw powders and a binder system. The composition of binder system plays an important influence on the properties of the final parts. In this study, IN718 feedstock were prepared using a newly developed wax-based binder system. IN718 tensile bar sample were sintered in different temperature and holding time, ranging from 1235°C - 1285°C for a dwell time range of 1 – 8 hours. Mechanical and microstructure properties, including tensile test, hardness, density, porosity, grain size, of the samples were conducted to evaluate the influence of sintering temperature and holding time. It is shown that sintering at 1245°C with 4 hours dwell time produced the best combination of UTS of 1400 MPa, YS of 550 MPa and 18% elongation. From the series of sintering profiles, it is proven that we can recreate samples with similar mechanical properties, which were collected from previous studies, using a lower temperature and shorter dwell time. This allowed us to conclude that the feedstock used in this experiment is comparable to past experiments’ and there are a lot of potential to the feedstock mixture in producing better mechanical properties.